Economic Analysis of Post-Harvest Loss and Marketing Efficiency in Guava (cv. Allahabad safeda) in Karnataka - T M Gajanana (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2015)
Post-harvest losses (PHL) in guava (cv. Allahabad safeda) were estimated at the field and retail levels in Karnataka, and impact of this loss on marketing efficiency was studied. Results indicated that the total PHL was 13.29% consisting of field-level loss (9.17%) and retail level loss (4.12%). The producer's share was 51.52% and PHL, when included as an item of cost, reduced the share to 45.80%. PHL also reduced marketing efficiency index from 1.06 to 0.88, thereby indicating the importance of PHL and scope for minimizing it to improve the efficiency of the marketing system in guava.